Balancing Taxation in the Indonesian P2P Lending Landscape: Ensuring Fair and Equitable Treatment - Widjiastuti, Agustin; Kartiko, Nafis Dwi (IHSA Institute, 2024)
This research aims to evaluate and compare the legal framework and tax policies of peer-to-peer lending (P2P lending) in various countries, using a normative juridical research approach. This research explores the tax implications and regulatory treatment of financial technology, particularly P2P lending platforms. The normative juridical research method focuses on the study of legal norms, principles, and doctrines. The results of this study show that there are significant similarities and differences in the VAT tax policies on P2P lending services in countries such as the European Union, Australia, Canada, and New Zealand. Each country recognises contributions under the P2P lending model as the provision of credit, which is generally exempt from VAT. However, there are differences in the treatment of the credit itself, eligibility for input tax credits, and the application of the principle of fiscal neutrality. From an Indonesian perspective, it is important to adapt tax regulations to digital innovations in the financial sector, considering the unique characteristics of technology-based financial services such as P2P lending. This policy should be able to address the complexity of services provided by P2P lending platforms and ensure fair and equitable tax treatment